Sustainable Marketing Strategies and Financial Performance: A bibliometric Analysis with Web of Science database - Sadriwala, Kaneez Fatima; Ahmed, Zunaith; Pradhan, Bijay Lal; Sadriwala, Muruf Fatima (Morgan Journal of Interdisciplinary Research Studies, 2024)
This comprehensive study explores the relationship between sustainable marketing strategies and financial performance within the evolving business landscape. It delves into the emergence of sustainable marketing as a powerful strategy that bridges consumer desires and responsible practices. Leveraging key findings from various research sources, the study underscores the significance of tangible sustainability efforts in meeting rising consumer, investor, and employee demands. It emphasizes the vital evolution of sustainable marketing practices and the shift from traditional marketing paradigms. The study highlights the major area of publication by journal, country, most popular articles and the funding agencies. Ultimately, the research identifies the need to investigate how sustainable marketing strategies impact financial performance, offering valuable insights for businesses aiming to navigate the nexus between profitability and responsible practices in today’s complex business environment.